Stress Coping Framework As an Effort To Improve Quality of Life Patients with Chronic Obstructive Pulmonary Disease: A Literature Review - Sutrisno, Sutrisno; Rondhianto, Rondhianto (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT  COPD patients usually experience a decrease in quality of life due to COPD symptoms such as coughing, shortness of breath,exacerbationAcute disease and comorbidities that occur in COPD patients cause limitations in daily activities. Stress coping is one of the factors that causes good or bad self-care behavior in COPD patients. To describe the influence, stress coping and level of selfcare in COPD patients on their quality of life. The method of this study is a literature review. Literature searches using electronic databases such as PubMed, Google Scholar and Science Direct. A literature review was carried out on international journals published in the last 5 years, available in full text. The keywords used were "self-care", stress coping" and "quality of life" for COPD patients. The selection of articles followed the PRISMA approach. This review summarizes eighteen articles. Five articles discussed self-care, the SelfEfficacy scale, and discriminative validity with higher self-care scale scores in individuals with greater COPD severity and poorer health status. Five articles discuss coping stress in COPD sufferers. COPD patients who have good knowledge will have more coping mechanism strategies so that their quality of life becomes more prosperous. Seven articles discussed the quality of life of COPD sufferers. If a COPD patient has good stress coping and strong confidence and confidence in his or her abilities, this will influence self-care actions and improve the COPD patient's quality of life. Future researchers are encouraged to explore similar research themes using other journal search engines to enrich the study. Keywords: Self Care, Stress Coping, Quality Of Life, COPD